The views of educators on the utilisation of information and communication technologies in controlled educational environments: The example of therapeutic communities - Ntaflou, Aikaterini; Malafantis, Konstantinos (Homo Virtualis, 2024)
Reintegration of individuals into the community constitutes an official strategic aim for correctional facilities. It methodically addresses the factors that contribute to the recurrence of delinquent behaviour while simultaneously reinforcing those that will aid in the stability of this integration. From this perspective, incarcerated individuals need to be educated on how society and the state operate. A crucial part of this education, not as a privilege but as a necessity for reintegration into a world where technological advancements affect the structure and functions of social systems, is familiarisation with Information and Communication Technologies (ICT). For this reason, educators who undertake the task of educating delinquent individuals have an exceptionally challenging job. They strive to prepare individuals who are already disadvantaged in various aspects of their lives for their return to society, in highly restrictive environments, both in terms of educational and technological infrastructure. This research is part of a postdoctoral study on education and reintegration. It focuses on the views of educators who teach in therapeutic reintegration communities regarding utilising information and communication technologies in the education provided in these structures. The method of interviews was used with a total of 8 educators teaching in therapeutic communities in Greece.